Differential Effect of Auxin on in Vivo Extensibility of Cortical Cylinder and Epidermis in Pea Internodes - Kutschera, Ulrich (1987)
The effect of auxin indole-3-acetic acid (IAA) on growth and in vivo extensibility of third internode sections from red light grown pea seedlings (Pisum sativum L. cv Alaska) and the isolated tissues (cortex plus vascular tissue = cortical cylinder, and epidermis) was investigated. Living tissue was stretched at constant force (creep test) in a custom-built extensiometer. In the intact section, IAA-induced increase in total (E(tot)), elastic (E(el)), and plastic (E(pl)) extensibility is closely related to the growth rate. The extensibility of the cortical cylinder, measured immediately after peeling of intact sections incubated for 4 hours in IAA, is not increased by IAA. Epidermal strips, peeled from growing sections incubated in IAA, show a E(pl) increase, which is correlated to the growth rate of the intact segments. The isolated cortical cylinder expands in water; IAA has only a small growth-promoting effect. The extensibility of the cortical cylinder is not increased by IAA. Epidermal strips contract about 10% on isolation. When incubated in IAA, they do not elongate, but respond with an E(pl) increase. The amount of expansion of the cortical cylinder and contraction of the epidermis (tissue tension), measured immediately following excision and peeling, stays constant during IAA-induced growth of intact sections. The results support the hypothesis that IAA induces growth of the intact section by causing an E(pl) increase of the outer epidermal wall. The driving force comes from the expansion of the cortical cylinder which is under constant compression in the intact section.